The Impact of Social Media on Political Enthusiasm Study of the Young Generation in the General Election of Jekan Raya City, Palangka Raya City - Febriantory, Febriantory; Antuhni, Tomi; Marhayadi, Marhayadi; Adiwijaya, Saputra; Batubara, Muhammad Zusanri; Saragih, Osi Karina (Eastasouth Institute, 2024)
General Election (Election) Young generation or millennials. General elections are a process to achieve integrity and legal authority which is carried out with the participation of candidates as well as the control process of the agency or field of supervision, to obtain legality by the public which is approved by the established law. Become an underlying part of democratic instruments. The general election indicator is community involvement and participation. This is with the involvement of young people or the millennial generation. The participation or involvement of young people or the millennial generation in general elections is very crucial because, apart from being large in number, these young people are also one of the nation's next generations. However, in terms of participation efforts and indications of what possibilities could have an impact on an outcome, it will certainly be influenced by the participation or involvement of young people. It needs to be identified so that in the future it can help their efforts regarding ways or procedures to take part in a correct election. This research was conducted in Jekan Raya Village, Palangkaraya City. The research findings illustrate that social media has a big influence on the millennial generation, especially in recognizing the profiles of candidates running for office.